1999
DOI: 10.1021/jm9901935
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Peptidomimetic Inhibitors of Protein Farnesyltransferase Demonstrating Improved Cellular Potency and Significant in Vivo Efficacy

Abstract: The synthesis and evaluation of analogues of previously reported farnesyltransferase inhibitors, pyridyl benzyl ether 3 and pyridylbenzylamine 4, are described. Substitution of 3 at the 5-position of the core aryl ring resulted in inhibitors of equal or less potency against the enzyme and decreased efficacy in a cellular assay against Ras processing by the enzyme. Substitution of 4 at the benzyl nitrogen yielded 26, which showed improved efficacy and potency and yet presented a poor pharmacokinetic profile. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Although there is no direct evidence that indicates how this type of molecule interacts with the enzyme, these data do not support the idea that the sulfur on the “left” portion of the inhibitors interacts with a metal atom. On the other hand, the difficulty which we and others have experienced finding useful replacements for the methionine portion of the inhibitor does suggest a vital role for the methionine atom. , It should also be considered that the requisite cyclohexylethyl portion of the compounds described in this paper might occupy the farnesylpyrophosphate binding site of FTase, but the kinetic experiments required to explore this issue have not yet been undertaken. It is interesting that compound 30 (IC 50 = 0.14 nM) contains all the structural elements of a transition-state analogue for the alkylation of CAAX with farnesylpyrophosphate.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Although there is no direct evidence that indicates how this type of molecule interacts with the enzyme, these data do not support the idea that the sulfur on the “left” portion of the inhibitors interacts with a metal atom. On the other hand, the difficulty which we and others have experienced finding useful replacements for the methionine portion of the inhibitor does suggest a vital role for the methionine atom. , It should also be considered that the requisite cyclohexylethyl portion of the compounds described in this paper might occupy the farnesylpyrophosphate binding site of FTase, but the kinetic experiments required to explore this issue have not yet been undertaken. It is interesting that compound 30 (IC 50 = 0.14 nM) contains all the structural elements of a transition-state analogue for the alkylation of CAAX with farnesylpyrophosphate.…”
Section: Resultsmentioning
confidence: 96%
“…Although the exact magnitude of the efficacy of FTase inhibitors has been difficult to reproducibly quantify, these results clearly demonstrate a measurable level of in vivo efficacy against human pancreatic cancer cells. Further in vivo efficacy studies with this type of FTase inhibitor will be reported in due course 26d…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations